PERAN PENDIDIKAN DALAM MEMBENTUK NILAI-NILAI SOSIAL DAN NILAI BUDAYA SISWA DI SD NEGERI 12 RANTAU ALAI - Anisah, Nia; Sartika, Sri Dewi; Wulandari, Rini (Jurnal Multidisipliner Kapalamada, 2024)
This study aims to understand the role of education in shaping students' social and cultural values. The role of education in shaping students' social and cultural values is very important. Character education given to students as the next generation of the nation leads to respect and honesty. Character education based on cultural values can help students understand and internalize values that are commonly accepted by society, such as justice, respect and honesty. Thus, students can become capable individuals in all aspects, including mental, social, and moral. Effective character education can help students develop the ability to practice their moral behavior through activities such as providing services, and help students understand the importance of social values in counteracting the influence of other incompatible values.